Breathable and Wearable Energy Storage Based on Highly Flexible Paper Electrodes. Issue 42 (30th August 2016) - Dong, Liubing; Xu, Chengjun; Li, Yang; Pan, Zhengze; Liang, Gemeng; Zhou, Enlou; Kang, Feiyu; Yang, Quan‐Hong
Abstract : Breathable and wearable energy storage is achieved based on an innovative design solution. Carbon nanotube/MnO2 ‐decorated air‐laid paper electrodes, with outstanding flexibility and good electrochemical performances, are prepared. They are then assembled into solid‐state supercapacitors. By making through‐holes on the supercapacitors, breathable and flexible supercapacitors are successfully fabricated.